Eleven on top - Evanovich, Janet (New York St. Martin's Press, 2005)
Hoping to discontinue her career as a bounty hunter for something safer, Stephanie Plum is inadvertently drawn into a case that is complicated by her tangled love life, her chaotic family, and her penchant for wrecking cars
Php 1347.50
Donated by Gorriceta-Rojo family 12.11.18
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Bounty hunters -- Fiction; New Jersey -- Fiction; Humorous fiction. gsafd; Mystery fiction. gsafd